Associations Between Childhood Learning Disabilities and Adult-Age Mental Health Problems, Lack of Education, and Unemployment. (January 2019) - Aro, Tuija; Eklund, Kenneth; Eloranta, Anna-Kaija; Närhi, Vesa; Korhonen, Elisa; Ahonen, Timo
We studied the impact of diverse subtypes of learning disabilities (LD) on adult-age mental health, education, and employment by comparing the LD group ( n  = 430) with a matched control group without a known history of LD ( n  = 2, 149). The clinical archived data were merged with lifelong register data on sickness allowances/disability pensions granted on the basis of psychiatric illnesses, reimbursements for psychoactive medication, having a degree after compulsory education, and having received unemployment allowances. Differences emerged between the LD and control groups in all outcomes, suggesting that a higher proportion of individuals with LD had mental health problems compared to the control group, and a notable share of them had not attained a degree after compulsory education and had been unemployed for an extended period. Subgroup comparisons indicated that math disability (MD) was associated with antidepressant use and unemployment, whereas the reading disability (RD) group showed the least problems with employment. Interactions between subgroup and gender suggested that MD (with/without RD) may pose a higher risk than RD for females, whereas RD seemed to pose a risk for males. The findings suggest the need for researchers, clinicians, and those involved with adult education to consider mental health and educational problems among individuals with LD.